Research on the participants’ strategy of pollution reduction and carbon reduction from the perspective of tripartite game - Wang, Shi-Jin; Zhang, Yu-Xin (Frontiers in Physics, 2025)
The treatment of pollution reduction and carbon reduction in Yongding River Basin involves many stakeholders. It is of great significance and value to analyze the pollution reduction and carbon reduction in Yongding River Basin by using game model, study different game scenarios and participants’ behavior choices and motivations, evaluate the results and effects of the game, and put forward the optimization and improvement scheme of the game. This paper constructs a tripartite game model involving the central government, local governments and river basin companies, and through numerical simulation analysis, reveals the decision-making evolution path and influencing factors of all parties in the implementation of pollution reduction and carbon reduction policies. The results show that the increase of financial subsidies provided by the central government, the improvement of the fine mechanism, the increase of the proportion of central subsidies paid by local governments to river basin companies and the reduction of the costs borne by local governments in implementing pollution reduction and carbon reduction policies can all promote the pollution reduction and carbon reduction actions of local governments and river basin companies. Based on the simulation of the above conclusions, it provides scientific theoretical support and policy suggestions for pollution reduction and carbon reduction in Yongding River Basin, thus forming the effect of joint efforts to enhance the coordinated governance of government and enterprises.